If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6u = 4u + -10 Reorder the terms: 6u = -10 + 4u Solving 6u = -10 + 4u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-4u' to each side of the equation. 6u + -4u = -10 + 4u + -4u Combine like terms: 6u + -4u = 2u 2u = -10 + 4u + -4u Combine like terms: 4u + -4u = 0 2u = -10 + 0 2u = -10 Divide each side by '2'. u = -5 Simplifying u = -5
| 5sin^2x+3sinx-1=0 | | X/2-10=25 | | 12+6+x= | | 97+x=90 | | P/3-2=5 | | 1.58x+y=90 | | 24n=-720 | | x-1112=8 | | -m=10-6m | | 32x+2=3x-2 | | x-5(4-x)=-38 | | 23-6x=-43 | | 123+123+123= | | 7-4(x+3)= | | 7c+12f=18 | | x-2(-3y)=10 | | X+100=90 | | 9+(4+S)= | | 6(1+2p)-6p=6p+6 | | 8b-4=3b-0.5 | | -75=-5(6m+5) | | 9/8÷3/4 | | k/3-6=12 | | 123+3x= | | (9x)/(4x) | | 5t=3t-4 | | 3+8(x)=3(2)(x)-1 | | 150=-16t^2+118t+3 | | 1/2a-4=3-1/4 | | 7+.2(x-1)=5+.3(x-1) | | 4/5×5 | | (16-9i)-(2-9i)= |